AN INVESTIGATION ON OFFSHORING AND RESHORING: IMPLICATIONS FOR THE UK ECONOMY - UCHE, N. CHINYERE (2015)
Many years have seen the offshoring phenomenon to be a continuous occurrence in different parts of the world because it yields major benefits for the firm carrying out the activity but the tide seems to be changing in the market today especially due to the identification of the hidden costs and other. The paper begins by discussing the concepts which are associated with the topic and the various progressions to which it occurs. The drivers to which have caused repatriation to the UK are similar to other counties but a few factors have being identified to be specific to just the UK. Hence, the factors to which drives reshoring were addressed while UK specific drivers such as brand name, quality, skill base and regulated legal frameworks which protects manufacturers were elaborated upon; some barriers which included high labour cost, taxes and energy cost were also identified by manufacturers whom considered repatriation to the UK.